2013
DOI: 10.1093/cvr/cvt144
|View full text |Cite
|
Sign up to set email alerts
|

Differential changes in titin domain phosphorylation increase myofilament stiffness in failing human hearts

Abstract: We conclude that hypo-phosphorylation of the N2-Bus and hyper-phosphorylation of the PEVK domain can act complementary to elevate passive tension in failing human hearts. Differential changes in titin-domain phosphorylation may be important to fine-tune passive myocardial stiffness and diastolic function of the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
130
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(142 citation statements)
references
References 31 publications
6
130
1
Order By: Relevance
“…Regarding to the magnitude of changes, previously published studies found similar differences as reported here. Increase in PEVK element phosphorylation (Ser-12742 in the rat sequence) was 31% in human HTN (45) and 23% in patients with dilated cardiomyopathy (26), being similar to the 32.6% in mRen2 rats as reported here. A more prominent change (ϳ70% decrease) in PEVK phosphorylation level was found in a different site within the PEVK region of titin (Ser-12884) in a metabolic model of HFpEF (19).…”
Section: Sd Mren2supporting
confidence: 87%
See 1 more Smart Citation
“…Regarding to the magnitude of changes, previously published studies found similar differences as reported here. Increase in PEVK element phosphorylation (Ser-12742 in the rat sequence) was 31% in human HTN (45) and 23% in patients with dilated cardiomyopathy (26), being similar to the 32.6% in mRen2 rats as reported here. A more prominent change (ϳ70% decrease) in PEVK phosphorylation level was found in a different site within the PEVK region of titin (Ser-12884) in a metabolic model of HFpEF (19).…”
Section: Sd Mren2supporting
confidence: 87%
“…We found increased phosphorylation at Ser-12742, without changes in the phosphorylation level of Ser-12884 in mRen2 hearts. PEVK Ser-12742 hyperphosphorylation was previously demonstrated in mice with transverse aortic constriction (22), in an old HTN dog model (18), as well as in human HF (17,26). Moreover, a recent translational work implicated the hyperphosphorylation of the very same site (Ser-12742) in human HFpEF (45).…”
Section: Sd Mren2mentioning
confidence: 85%
“…140 This serine was confirmed to be PKA/PKG dependently phosphorylated in a recent mass spectrometric analysis of recombinant N2-Bus. 123 This analysis identified additional phosphosites within N2-Bus, including evolutionary conserved S4010 (PKA-dependent) and S4099 (PKG-dependent), as well as nonconserved S4065 (PKA-dependent) and S4092 (PKG-dependent). ERK2 was also shown in vitro to phosphorylate S4010 within the N2-Bus, along with nonconserved S3918 and S3960.…”
Section: Regulation Of Titin Stiffness By Phosphorylation: Facts and mentioning
confidence: 98%
“…123,[137][138][139][140] Recent work on titin phosphorylation has focused mainly on the disordered spring elements, N2-Bus and PEVK, both of which are substrates of several major PKs activated by well-studied signaling pathways (Figure 6). N2-Bus is phosphorylated in vitro not only by PKA but also by cGMP-dependent PKG, 123,140 ERK2, 141 and the δ-isoform of Ca 2+ /calmodulin-dependent PK-II, Ca 2+ /calmodulin-dependent protein kinase-IIδ (CaMKIIδ). 142,143 The PEVK region is also phosphorylated by CaMKIIδ 142,143 and PKCα.…”
Section: Regulation Of Titin Stiffness By Phosphorylation: Facts and mentioning
confidence: 99%
“…For example, Wolfgang Linke and his group work on the giant protein titin which is very sensitive to even very low levels of proteases, so they reasonably assumed that only biopsy samples were likely to be free of degradation. Thus, several years passed before it was discovered (Krüger et al 2009;Hamdani et al 2013;Koetter et al 2013) that the titin in our donors were indeed free of proteolysis. RNAs are also highly sensitive to hydrolysis, but several colleagues have used LV samples from failing and donors with good results including Kuster et al (2013), Kong et al (2010) and Huang et al (2016).…”
Section: Donor Heartsmentioning
confidence: 89%